MODEL KEPEMIMPINAN GEREJAWI YANG BERAKAR PADA NILAI-NILAI BUDAYA LOKAL - Jhesica Patalo; Asildan Bungan Layuk; Arya Arnal Anugrah; Selfester Morna; Febriana Efrin (Adisam Publisher, 2025)
This article aims to examine a model of church leadership rooted in local cultural values as a contextual approach to addressing the challenges of ministry within Indonesia's multicultural society. This approach is based on the understanding that the church does not exist in a vacuum, but rather within a specific social and cultural context that shapes the way its members think, act, and believe. Using descriptive qualitative methods using interviews, participant observation, and literature review, this study found that cultural values such as deliberation, mutual cooperation, respect for traditional leaders, and traditional social structures have influenced the way leadership is exercised in local churches. Church leadership in this context has a dual function: as a spiritual and social figure, bridging the Christian faith with the realities of everyday life. However, the process of inculturating cultural values into church leadership is not without challenges, particularly in maintaining theological fidelity to biblical teachings without falling into syncretism. Therefore, church leadership development strategies must be directed toward contextual, collaborative development based on in-depth theological reflection. In this way, the church can realize leadership that is not only socially effective, but also spiritually faithful in answering the call to service in society.